Contamination of water and soil of rice fields with soil transmitted helminths as source of transmission to farmers in Grogol sub-district, Kediri district - Siti Munawaroh; Heny Arwati; Puspa Wardhani (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACTSoil-transmitted helminths (STH) are the worms which transmitted through the soil. The people of Dusun Semen, Grogol, Kediri have a habit of defecating in the river. Farmers who work in direct contact with water and soil is possible to be infected with STH. The purpose of this study was to determine STH species in water, soils, and farmer's fecal samples. Water samples were collected from three spots of river A and B, soil samples from 43 rice fields, and fecal samples from 50 farmers. Water samples were examined by sedimentation, soil samples by floatation, and fecal samples by Kato-Katz method. The data were then analyzed by Chi square test. Out of 18 water samples, 12 samples (66.7%) were positive, consisted of 4 samples (22.2%) contained of Ascaris lumbricoides and 8 samples (44.4%) contained Trichuris trichiura. Total soil samples were 129, where 8 samples (6.2%) were positive for A. lumbricoides, and 10 samples (7.7%) for T. trichiura. Out of 50 villagers, only 39 gave the fecal samples, where 12 samples (31.0%) were positive consisted of 5 samples (12.8%) for A. lumbricoides, 8 samples (20.5%) for T.trichiura. In conclusion, the STH species found in the media of water, soil, and feces of farmers are the similar namely A. lumbricoides and T. trichiura. Positive farmer samples prove STH transmission from STH contaminated water and soil.Keyword: Water, soil, feces, soil transmitted helminths